2012
DOI: 10.1080/13506285.2011.626466
|View full text |Cite
|
Sign up to set email alerts
|

The role of surface feature continuity in object-based inhibition of return

Abstract: The contribution of surface feature continuity to object-based inhibition of return (IOR) was tested in three experiments. Participants executed a saccade to a previously fixated or unfixated colored disk after the object had moved to a new location. Object-based IOR was observed as lengthened saccade latency to a previously fixated object. The consistency of surface feature (color) and spatiotemporal information was manipulated to examine the feature used to define the persisting objects to which inhibition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
23
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 24 publications
6
23
1
1
Order By: Relevance
“…The lack of an effect of color change, while consistent with previous studies using the reviewing paradigm, is inconsistent with Tas et al’s (2012) finding that color change reduces IOR – a finding that the authors attributed to a disruption of perceptual continuity in the color change condition. There are several important differences between the experiments, however, that may contribute to the divergent results.…”
Section: Discussionsupporting
confidence: 44%
See 4 more Smart Citations
“…The lack of an effect of color change, while consistent with previous studies using the reviewing paradigm, is inconsistent with Tas et al’s (2012) finding that color change reduces IOR – a finding that the authors attributed to a disruption of perceptual continuity in the color change condition. There are several important differences between the experiments, however, that may contribute to the divergent results.…”
Section: Discussionsupporting
confidence: 44%
“…While robust across the object file literature – particularly in studies using the classic reviewing paradigm – the results suggesting a limited representation or use of color information is at odds with a number of studies demonstrating episodic representations of color (e.g., Johnson, Hollingworth, & Luck, 2008; Tas, Dodd, & Hollingworth, 2012) and their use in the operations that preserve object continuity (e.g., Richard et al, 2008). These conflicting results may reflect the fact that studies using the reviewing paradigm (that have suggested a critical role for identity, but not color) have most often used as the primary task identification of the target object.…”
mentioning
confidence: 84%
See 3 more Smart Citations